2011
DOI: 10.1080/10447318.2011.540491
|View full text |Cite
|
Sign up to set email alerts
|

A Visual Information Processing Model to Characterize Interactive Visualization Environments

Abstract: Interactive visualizations have the potential to greatly enhance our ability to analyze data. Although the user is central to the use of such environments, perceptual and cognitive processes are not well understood within the context of interactive visualization. Although cognitive psychology has provided a greater understanding of visual perception and cognition, a theoretical framework that links this knowledge with the interactive visualization process is needed. This article aims to fill this gap by introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 68 publications
0
8
0
5
Order By: Relevance
“…Several frameworks have been suggested to explain why visual representation could enhance performance (Jun, Landry, & Salvendy, 2011;Ntuen, Park, & Gwang-Myung, 2010). However, studies comparing graphs and tables reported mixed results: Some reported that graphs are better than tables, but the others reported opposite results.…”
Section: Evaluation Of Tabular Visualizationsmentioning
confidence: 87%
“…Several frameworks have been suggested to explain why visual representation could enhance performance (Jun, Landry, & Salvendy, 2011;Ntuen, Park, & Gwang-Myung, 2010). However, studies comparing graphs and tables reported mixed results: Some reported that graphs are better than tables, but the others reported opposite results.…”
Section: Evaluation Of Tabular Visualizationsmentioning
confidence: 87%
“…For example, "certain features [in visualizations] appear to guide visual attention very quickly and without focused attention. That is, we attend to these features, whether we are consciously attending to them or not" [10]. Dual Coding Theory, e.g., states that visualizations can improve memorability simply by providing an alternative way to retrieve memories [12].…”
Section: Visualizationmentioning
confidence: 98%
“…Some examples for different visualization types are graph models [9], interactive visualizations [10], or videos [11]. A common element in all visualization types is that they affect the perception and cognitive processing of information (to a varying degree).…”
Section: Visualizationmentioning
confidence: 99%
“…As propriedades interativas são pouco exploradas pelos referidos trabalhos em razão da utilização de baixas resoluções de dados, majoritariamente. No entanto,é notório que as representações visuais devem ser capazes de atender novas indagações decorrentes das análise visuais [Card et al, 1999;Jun et al, 2011;Ware, 2004]. O envolvimento com os dados proporcionado pela interatividadeé crítico na avaliação visual da qualidade dos dados [Heer e Shneiderman, 2012].…”
Section: Justificativa Da Hipóteseunclassified
“…O mapeamento visual -ou rendering -aplica técnicas de computação gráfica sobre a imagem preliminar criada pelo mapeamento geométrico para acrescentar propriedades visuais relacionadas a textura, a sombra e a luz [Telea, 2008] [Jun et al, 2011;Sedig et al, 2014;Yi et al, 2007Yi et al, , 2008, conforme será explorado na Seção 2.4.3.…”
Section: Transformações De Mapeamento Visualunclassified